Analysis Of How To Process Devices That Receive Electricity From Wind Energy. (Texas Journal of Engineering and Technology, 2024)
The article examines the vertical axis wind turbine, as well as its aerodynamic properties. Wind turbine parameters are calculated and the relationship between them and wind generator efficiency.